Rethinking the Concept of Learning in the Age of Artificial Intelligence: The Possibilities and Limitations of Human Education - Ghasemi, Shakiba; Izadpanah, Amin (Assessment and Practice in Educational Sciences, 2026)
Artificial intelligence, as one of the most transformative technologies of the present era, has had a profound impact on learning and education processes and is redefining the role of humans, teachers, and educational systems. The aim of this research is to rethink the concept of human learning in the era of artificial intelligence and to explain the opportunities, challenges, and ethical-educational requirements arising from it. The research is fundamental and was conducted with an interpretive qualitative approach combining library research and semi-structured interviews. In the library section, data were extracted from a targeted review of scientific sources between 2019 and 2025, and in the qualitative section, semi-structured interviews were conducted with 16 experts in the fields of education, technology, and AI ethics. Data analysis for the qualitative part was conducted based on Braun and Clarke's (2006) six-step method, and main themes were extracted. The research findings showed that artificial intelligence increases the capacity to improve learning by providing contexts such as personalized learning, intelligent assessment, and real-time feedback. At the same time, it also has limitations and challenges. These limitations and challenges include data bias, privacy violations, weakening of the teacher's role, and cultural incompatibility. As a result, it can be said that learning in the age of artificial intelligence, along with the opportunities and possibilities it creates, also has challenges and limitations. By strengthening opportunities and properly managing challenges, the capacities of artificial intelligence can be used for growth, justice, and excellence in human education.